Fusion CRT pacing: septal flash significance in super responder patients. (3rd October 2022) - Vacarescu, C; Luca, C T; Gaita, D; Crisan, S; Mornos, C; Goanta, E V; Lazar, M A; Ionac, I; Arnautu, D A; Cozma, D
Abstract: Background: LV only CRT pacing is an option that may be considered to maximize response to CRT and at least as an alternative in non-responders to biventricular (BiV) pacing. However, criteria to best titrate therapy on an individual basis are lacking in fusion pacing. On the other hand, septal flash (SF) is a strong predictor of favorable response for patients (pts) with BiV pacing. Purpose: To analyze the relationship between SF and the response to fusion CRT pacing. Methods: Consecutive pts with exclusive fusion CRT-P were included. Right atrium/left ventricle leads DDD CRT pacing system were used in all patients. Prospective data were collected at every 6 months follow-up visits: device interrogation, exercise test, echocardiographic parameters. Exercise tests, device reprogramming and medication optimization were performed regular in order to maximize CRT response. Patients were divided in 2 groups: super-responders (SR) and responders (R). SRs were defined those with left ventricular end-systolic volume (LVESV) improvement ≥30% and stable ejection fraction (LVEF) ≥45%. Results: 69 pts with NYHA II–III heart failure and non-ischemic dilated cardiomyopathy were initially included. 5 pts were non responders and excluded (non LBBB, spontaneous QRS <149 ms). Final analyzed group had 64 pts (35 male) aged 60±12 y.o. The mean follow-up was 54±19 months; 22 pts (34%) were SRs. At baseline, SF was found in all SR pts and in 55% of R pts. SF was corrected post CRT in all patients, except one. For this patient (LV lead in a posterior branch of the coronary sinus – CS) the strategy included an upgrade to triple chamber device with a second lead in a lateral branch of the CS and became SR from R. Mitral regurgitation decreased in 38 patients (all SR, 40% R). Interesting, baseline left atrium volume and pulmonary sistolic artery pressure were smaller in SR versus R group, however SF did not corelate with LA volume/diastolic dysfunction. Conclusions: Septal flash seems to be a strong predictor of super-response in patients with fusion CRT pacing. This finding could improve the selection of candidates for fusion CRT-P, however larger studies are needed to assess SF in this categories of patients. Funding Acknowledgement: Type of funding sources: None.